Health care accessibility and mobility in breast cancer: a Latin American perspective - André Ferreira Azeredo-; Bruna Stella Zanotto; Flavia Martins; Nádia Navarro; Rafaela Alencar; Clarissa Medeiros (BMC, 2024)
Abstract Background Latin America (LATAM) encompasses a vast region with diverse populations. Despite publicly funded health care systems providing universal coverage, significant socioeconomic and ethno-racial disparities persist in health care access across the region. Breast cancer (BC) incidence and mortality rates in Brazil are comparable to those in other LATAM countries, supporting the relevance of Brazilian data, with Brazil's health care policies and expenditures often serving as models for neighboring countries. We evaluated the impact of mobility on oncological outcomes in LATAM by analyzing studies of patients with BC reporting commuting routes or travel distances to receive treatment or diagnosis. Methods We searched MEDLINE (PubMed), Embase, Cochrane CENTRAL, LILACS, and Google Scholar databases. Studies eligible for inclusion were randomized controlled trials and observational studies of patients with BC published in English, Portuguese, or Spanish and conducted in LATAM. The primary outcome was the impact of mobility or travel distance on oncological outcomes. Secondary outcomes included factors related to mobility barriers and access to health services. For studies meeting eligibility, relevant data were extracted using standardized forms. Risk of bias was assessed using the Newcastle-Ottawa Scale. Quantitative and qualitative evidence synthesis focused on estimating travel distances based on available data. Heterogeneity across distance traveled or travel time was addressed by converting reported travel time to kilometers traveled and estimating distances for unspecified locations. Results Of 1142 records identified, 14 were included (12 from Brazil, 1 from Mexico, and 1 from Argentina). Meta-analysis revealed an average travel distance of 77.8 km (95% CI, 49.1-106.48) to access BC-related diagnostic or therapeutic resources. Nonetheless, this average fails to precisely encapsulate the distinct characteristics of each region, where notable variations persist in travel distance, ranging from 88 km in the South to 448 km in the North. Conclusion The influence of mobility and travel distance on access to BC care is multifaceted and should consider the complex interplay of geographic barriers, sociodemographic factors, health system issues, and policy-related challenges. Further research is needed to comprehensively understand the variables impacting access to health services, particularly in LATAM countries, where the challenges women face during treatment remain understudied. Trial registration CRD42023446936.